ETIKA BISNIS ISLAMI DALAM PRAKTEK BISNIS RASULULLAH - Muhammad Saifullah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
Historical study of the Muhammad’s behavior and business ethics before being appointed as messenger is an interesting study, because the conduct and business ethics that Mohammed applied was based on the study of the verses of the Koran. After appointed as messenger (40 years old), the life of prophet Muhammad was more guided by the revelations of the Qur'an. Some principles which the prophet applied are honest, amanah, accurate in weighting, avoid gharar, not hoard goods, not execute al-ghab and tadlis among seller and buyer.